Profil Hematologi Tikus (Rattus norvegicus Berkenhout, 1769) Galur Wistar Jantan dan Betina Umur 4, 6, dan 8 Minggu - Fitria, Laksmindra; Sarto, Mulyati (Biogenesis, 2014)
Animal model is very important in biomedical research. Prior to apply in human or otherÂ primates, experiments using lower animals model such as rodents must be conducted (preclicicalÂ studies). Wistar rats (Rattus norveg